Pemanfaatan Sinyal Ekspansi Radius Berbasis Konektivitas Bluetooth Menggunakan Antenna Eksternal Pada Sistem Pengendalian Pencahayaan - Williyandi, Rizky; Liza, Risko; Suriati, Suriati (Universitas Islam Negeri Sumatera Utara, 2023)
Control of the lighting system is a form of implementation of a home control system that is categorized into the form of IoT in the lamp category, this system provides convenience to homeowners, namely users to be able to control home lights using an Android smartphone. In designing the system, the author implements the switch on the lamp to be replaced by using a relay device which is controlled via a microcontroller device based on a Bluetooth connection so that it can be connected to an Android smartphone that has been configured in the lighting control program application using Bluetooth. The design is carried out using a qualitative-based development method. The results of this test provide data in the form of each type of antenna such as yagi, parabolic, and helix giving different connectivity test results in tests carried out in open spaces. Keywords: Android, Mikrokontoler, Relay, Bluetooth,Antena